João e o pé de feijão - Alcantara, Stefanny Doruti; Signori, Márcia Cristina Vieira Gonçalves; Lima, Cinthya Belussi Ribeiro; Guimarães, Renata maria de Sousa; Lopes, Cleuza Francisca da Silva; Lima, Maria dos Santos; Simião, Regina Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf